Studi Eksperimen Pengaruh Variasi Kecepatan Potong dan Kedalaman Pemotongan Terhadap Kekasaran Permukaan Benda Kerja Hasil Pembubutan Material Baja ST 41 Menggunakan Pahat HSS - -, Ardyan; -, Erwansyah; Arriyani, Yang Fitri (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2021)
The benchmark for the results of the machining process can be seen from the results of the products, one of which is the level of surface smoothness. The purpose of this experimental research is to find out how much cutting speed (Vc) and depth of cutting produce a workpiece with the smoothest level of surface roughness for the turning process carried out by students at the Bangka Belitung State Manufacturing Polytechnic Workshop. This research is using experimental method. The cutting speeds (Vc) used were 23 m/min, 24 m/min, 25 m/min, the cutting depths used were 0.5 mm, 0.8 mm, and 1.0 mm and the feeding speed was set at 0.040 mm/rev. The results showed that the best turning results using a cutting speed (Vc) of 23 m/min was using a cutting depth of 0.5 mm with a roughness value (Ra) of 1.372 m, using a cutting speed (Vc) of 24 m/min using a depth of cut. 0.5 mm with a roughness value (Ra) of 1.189 m and using a cutting speed (Vc) of 25 m/min using a depth of 0.5 mm with a surface roughness value (Ra) of 3.14 m. The lowest value for the level of surface roughness of the turning process was obtained using a cutting speed (Vc) of 24 m/min with a depth of 0.5 mm with a surface roughness value (Ra) of 1.189 m.